Terminal uridyltransferase 7 regulates TLR4-triggered inflammation by controlling Regnase-1 mRNA uridylation and degradation - Chia-Ching Lin (Nature Portfolio, 2021)
Terminal uridyltransferase 7 (TUT7) adds U-tails on diverse RNAs to promote degradation. Here the authors show that TUT7 is induced upon LPS treatment in macrophages and promotes decay of Regnase-1, thereby regulating the expression of a subset of cytokines, including IL-6.